Gestational Follow-up in Ewes - Placentome Size and Fecal Progesterone Metabolite Levels - Smangorzevski Muller, Lívia; Gonçalves de Faria Júnior, Wilson; Lima Meneses , Beatriz; Paixão dos Santos, Mainne; Pereira Braz Neto, Ismael; de Souza Amaral, Rodrigo; Santos, Fernanda Carlini Cunha (Acta Scientiae Veterinariae, 2023)
Background: Transabdominal ultrasonography in sheep allows real-time diagnosis and monitoring of pregnancy as well as measurement of the size of placentomes, which are structures that connect the fetal and maternal portions, that increase as pregnancy progresses. Progesterone is involved in the maintenance of pregnancy, with high levels noted during pregnancy, reaching a maximum concentration in the final 3rd trimester and declining close to delivery. In this context, it is hypothesized that measurements of placentome and progesterone levels could help in monitoring pregnancy in sheep. Therefore, the main objectives of this study included evaluating whether placentome size and fecal progesterone levels are associated with gestational age in ewe and whether measurement of the placentome size and fecal progesterone levels could be used as an estimate of gestational age. Materials, Methods & Results: A total of 63 pregnant adult Santa Inês ewes (between 2 and 5 years of age) in the city of Boa Vista, Roraima, were monitored. All ewes were kept in the paddock with Panicum maximun cv. tanzania, mineral salt, and water ad libitum, supplemented with 200 g/animal/day of soybean residue. Ewes were subjected to ultrasonography every 21 days from day 42 of pregancy until term to monitor pregnancy. Fecal samples were collected for measurement of progesterone level in the same moment. Ultrasonography was performed using a linear probe to measure the placentome, including length × width in centimeters. Placentomes that were close to the fetus were examined. Feces samples were collected directly from the rectal ampulla, stored individually in plastic bags, and frozen at -20ºC until processing. In the laboratory, these feces samples were freeze-dried and subjected to hormonal extraction with 80% methanol. Then, the levels of fecal progesterone metabolites were measured by enzyme immunoassay. Data was tabulated and submitted to statistical analyses, including descriptive stastistic, correlation, Kruskal-Wallis test and Tukey’s test. The levels of fecal progesterone metabolites increased significantly between the 3rd and 4th months of pregnancy, with a decrease close to delivery. Placentome size increased significantly between the second and third months of pregnancy. Placentome measurements did not correlate with progesterone levels and showed a weak correlation with gestational age. Therefore, we concluded that the measurements of placentome size and a single evaluation of fecal progesterone metabolites were not considered efficient methods for estimating gestational age. Discussion: Measurement of progesterone level in fecal samples is a non-invasive hormone monitoring method that provides values like that of blood levels and is less stressful for the animals at the time of sample collection. this wide physiological variation makes it difficult or even useless to use fecal progesterone, when is measured only once per animal, as an indicator of the presence of pregnancy. Despite this limitation, serial sampling is useful for monitoring of hormones during the pregnancy period and is an important tool for study purposes. Placentome size measurements correlated weakly with gestational age and did not correlate with progesterona level. Thus, the presence of placentomes is indicative of the presence of pregnancy but was considered inefficient for determining gestational age in sheep. Keywords: hormones, pregnancy, sheep, ultrasound.